Optimization of Adsorption and Desorption Time in the Extraction of Volatile Compounds in Brewed Java Arabica Coffee Using the HS-SPME/GC-MS Technique - Lidwina Angelica Soetantijo; Hendrik O. Lintang; Heriyanto Heriyanto; Mitha Ayu Pratama Handojo; Tatas Hardo Panintingjati Brotosudarmo (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The headspace solid phase microextraction (HS-SPME) technique has been recognized as a reliable technique for characterizing the aroma profile of Arabica coffee beans. The amount and content of the detected volatile compounds depend on the volatile analyte extraction process with HS-SPME, namely the adsorption and desorption processes. However, the optimal extraction time in applying coffee volatile compounds is still limited. This research aimed to obtain the optimum adsorption and desorption time in analyzing volatile compounds in brewed Java Arabica coffee. The adsorption time was optimized for 20 to 60 minutes with 5 minutes desorption time. The desorption time was optimized from 5 to 45 minutes with a 20 minutes of adsorption time. There are 14 volatile compounds with a peak area percentage of more than 2% from adsorption and desorption optimization. The optimal adsorption time was 50 minutes, where there were 5 of 7 compounds with the most significant area, such as 2-furfural (29%), 2-acetyl furan (3%), 2-furfuryl acetate (6%), 5-methyl furfural (12%), and 2-furfuryl alcohol (14%). Meanwhile, the most optimal desorption time was 5 minutes which detected 12 compounds, while the other desorption time only detected eight compounds. Furfuryl formate (2%), pyridine (12%), and 2-furfuryl alcohol (14%) had a higher peak area than the other compounds at a desorption time of 5 minutes. The results showed the same number of volatile compounds at each adsorption time. In conclusion, the adsorption time did not affect the number of compounds detected as in the optimization of desorption time. Adsorption and desorption time is crucial in analyzing volatile compounds from coffee using the HS-SPME/GC-MS technique.